The South American ancestry of the North Patagonian Massif: geochronological evidence for an autochthonous origin? - Rapalini, Augusto Ernesto (2013)
New U-Pb and 40Ar/39Ar age data from deformed and undeformed granitoids of the North Patagonian Massif establish the presence of Early Cambrian and widespread Ordovician magmatism in northern Patagonia. These data suggest that the Pampean (Cambrian) and Famatinian (Ordovician) magmatic belts of the Sierras Pampeanas are continuous into Patagonia. SHRIMP U-Pb age spectra from detrital zircons of Cambro-Ordovician metasedimentary rocks show patterns very similar to those from equivalent units of the Pampia block, over 500 km farther north. These results suggest that the North Patagonian Massif was likely part of the South American margin of Gondwana in the early Palaeozoic and strongly argue in favour of an authochtonous or para-autochthonous origin for this block.